Adaptive Personality Traits and Psychosocial Correlates among Living Kidney Donors - Pollmann, Iris; Gueler, Faikah; Mikuteit, Marie; Nöhre, Mariel; Richter, Nicolas; Weissenborn, Karin; de Zwaan, Martina (Frontiers in Psychiatry, 2017)
Since living kidney donors have repeatedly been shown to be mentally more healthy compared to the general population, they might also exhibit more adaptive personality characteristics. We investigated the personality traits of 315 living kidney donors (202 female and 113 male donors) on average 7.1 years after donation using the NEO-Five Factor Inventory, a frequently used personality inventory measuring the “big five” dimensions of personality (neuroticism, extraversion, openness, agreeableness, and conscientiousness). In addition, levels of depression, anxiety and fatigue were assessed with the PHQ-9, GAD-7 and MFI-20. Kidney donors showed more adaptive personality traits with higher agreeableness and lower neuroticism scores compared to the German general population. This was even more pronounced in living kidney donors with a high motivation to donate again (non-regreters). Scores for depression, anxiety, and fatigue did not differ from general population values and were significantly correlated with most personality dimensions. The more adaptive personality characteristics of living kidney donors might either be a selection effect or the consequence of the experience of donation and improved health of the close relative. Regardless of the causal relationship, adaptive personality traits might positively influence both physical and psychosocial wellbeing of the donor. Longitudinal studies should investigate if living donation might lead to persistent adaptive changes in personality traits.